Verification of interactions between silica and epoxidised squalene as a model for epoxidised natural rubber - Kaewsakul W et al (Journal of Rubber Research, 2014)
Unmodified squalene (Sq) and epoxidised squalene (ESq), as models for natural rubber and epoxidised natural rubber, were mixed with silica in a reactor at 140-145 degree C, which corresponds to the optimal mixing dump temperature of silica-filled natural rubber or epoxidised natural rubber compounds. The mixtures were prepared with and without bis-(triethoxysilylpropyl) tetrasulphide (TESPT) silane coupling agent. The bound silica in the mixtures was extracted and checked for its composition by using Fourier-transform infrared (FTIR) spectroscopy. The results indicate that Sq and ESq with the help of TESPT can chemically link to the silica surface, as the FTIR spectra of purified bound silicas show absorption peaks of hydrocarbon structures. The epoxidised squalene also produces chemical interaction with silica in the absence of TESPT, but to a lesser extent compared to the one with TESPT, as indicated by the absorption intensity. On the other hand, the silica in the Sq mixture without TESPT shows no trace of hydrocarbon, indicating that there is no noticeable chemical interaction involved.
Source Year: 2014
Keywords: Epoxidised natural rubber; Interactions; Model compound; Silane; Silica